PENGARUH NPL, CAR, INFLASI, SUKU BUNGA DAN KURS MELALUI JUMLAH PENYALURAN KREDIT TERHADAP PROFITABILITAS PERBANKAN - Zattira, Reza (Relasi : Jurnal Ekonomi, 2016)
This study was conducted to examine the effect of Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), inflation, interest rates and exchange rate through credit expansion to profitability of banks. The samples are ten biggest asset banking company’s in Indonesia in 2011-2014, using purposive sampling technique. This research method by using path analysis or path analysis. Test the hypothesis by using statistical t-test to test the partial coefficients, as well as statistical F test to determine the effect of jointly using a 5% significance. It also made the classic assumption test including normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. During the period show that the study data were normally distributed. Based normality test, multicollinearity, heteroscedasticity test and autocorrelation test found no deviation from the classical assumptions. The results showed that the variable NPL has a negative influence significantly to amount of lending, but CAR, sensitivity of interest rate, sensitivity of inflation, sensitivity of exchange rate have no effect on the amount of lending. In addition the results of this study indicate that the NPL, CAR, of interest rate, sensitivity of inflation, sensitivity of exchange rate have no effect on ROA, besides the amount of lending has positive effect on profitability of ROA.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />